Transcriptome and co-expression network revealed molecular mechanism underlying selenium response of foxtail millet (Setaria italica) - Wen, Yinyuan; Cheng, Liuna; Zhao, Zeya; An, Mengyao; Zhou, Shixue; Zhao, Juan; Dong, Shuqi; Yuan, Xiangyang; Yin, Meiqiang (Frontiers in Plant Science, 2024)
Introduction: Selenium-enriched foxtail millet (Setaria italica) represents a functional cereal with significant health benefits for humans. This study endeavors to examine the impact of foliar application of sodium selenite (Na2SeO4) on foxtail millet, specifically focusing on selenium (Se) accumulation and transportation within various plant tissues.To unravel the molecular mechanisms governing selenium accumulation and transportation in foxtail millet, we conducted a comprehensive analysis of selenium content and transcriptome responses in foxtail millet spikelets across different days (3, 5, 7, and 12) under Na2SeO4 treatment (200 μmol/L).Results: Foxtail millet subjected to selenium fertilizer exhibited significantly elevated selenium levels in each tissue compared to the untreated control. Selenate was observed to be transported and accumulated sequentially in the leaf, stem, and spikes. Transcriptome analysis unveiled a substantial upregulation in the transcription levels of genes associated with selenium metabolism and transport, including sulfate, phosphate, and nitrate transporters, ABC transporters, antioxidants, phytohormone signaling, and transcription factors. These genes demonstrated intricate interactions, both synergistic and antagonistic, forming a complex network that regulated selenate transport mechanisms. Gene coexpression network analysis highlighted three transcription factors in the tan module and three transporters in the turquoise module that significantly correlated with selenium accumulation and transportation. Expression of sulfate transporters (SiSULTR1.2b and SiSULTR3.1a), phosphate transporter (PHT1.3), nitrate transporter 1 (NRT1.1B), glutathione S-transferase genes (GSTs), and ABC transporter (ABCC13) increased with SeO4 2-accumulation. Transcription factors MYB, WRKY, and bHLH were also identified as players in selenium accumulation.This study provides preliminary insights into the mechanisms of selenium accumulation and transportation in foxtail millet. The findings hold theoretical significance for the cultivation of selenium-enriched foxtail millet.